Question:
Two rectangular picture frames have the same area of 45 square inches but have different side lengths. Frame A has a length of 6 3/4 inches, and Frame B has a length of 7 1/2 inches.
Answer:
1. the longer frame (B) has the shorter width
2. the shorter width is 6 3/7 inches, area divided by length
Step-by-step explanation:
The relation between area, length, and width is ...
A = LW
Then the width is ...
W = A/L . . . . . inversely proportional to length
1. Since length and width are inversely proportional (when area is constant), the shorter width will be associated with the longer length. Frame B will have the shorter width.__
2. The width of frame B is ...
W = A/L = (45 in²)/(7 in) = 45/7 in = 6 3/7 in
-Alan Becker
Please help me with this Math question.
Each win is worth 3 points.
Each draw is worth 1 point.
Each lose is worth 0 points.
Is 33 correct answer?
Answer:
33 is definitely the correct answer
Ill do anthing please help!!
Answer: 2π ft^2
Step-by-step explanation:
Area of a circle= π x the radius ^2
here your diameter is 4, and the radius is equivalent to half of the diameter so your radius equals 2.
A= π x 2^2
Find the area of the composite figure.
A. 122.5 sq ft
B. 171.5 sq ft
C. 196 sq ft
D. 296. 5 sq ft
Answer:
I think B is your answer if so then comment me and you can mark me as brainliest and please follow me
DOES ANYONE KNOW THE ANSWERS TO THESE PROBLEM, PLZ HELP!
Answer:
Q.1.
Sum of angles of a triangle = 180°
∠A + ∠B + ∠c = 180
(3x - 9) + (4x + 15) + 90 = 180
3x - 9 + 4x + 15 + 90 = 180
7x + 96 = 180
7x = 84
x = 12
∠A = 3x - 9 = 3(12) - 9 = 36 - 9 = 27°
∠B = 4x + 15 = 4(12) + 15 = 48 + 15 = 63°
∠A = 27°
∠B = 63°
Q.2.
[tex]using \ pythagoras \ theorem \\x^2 = 7^2 + (7\sqrt{3} )^{2} = 49 + 49(3) = 196\\x = \sqrt{196} = 14[/tex]
[tex]sin y = \frac{opposite}{hypotenuse} = \frac{7\sqrt{3} }{14} = \frac{\sqrt{3} }{2} \\\\y = sin^{-1} (\frac{\sqrt{3} }{2} ) = 60[/tex]
x = 14
y = 60°
5. A cabin rental costs $100 deposit plus $75 per day. Find the cost of renting a cabin for the
month of June.
Answer:
the answer to this question is $2,350
Step-by-step explanation:
june has 30 days so $75 × 30 + $100 = $2,350
Please help me I've been on this question for like and hour-
Answer:im so sorry i dont know this one
Step-by-step explanation:but i would try adding subtracting or divison
Answer:
21
Step-by-step explanation:
We can use a proportion to solve this problem
8 : 33.6 = 5 : OP
OP = (33.6 x 5)/8 = 21
Which of the below is the correct name for a plane that contains points A, B, C, and D?
plane CDE
plane CD
⭐️plane ACD
plane A
Answer:
Step-by-step explanation:
g Around 20 years ago, the CDC learned of an outbreak of gastrointestinal illness in several Georgia elementary schools. The CDC began their investigation by examining a random sample of 452 children. Among these children, 145 out of 304 became ill after eating burritos served by their school's cafeteria. On the other hand, only 20 of the remaining 148 who did not eat burritos became ill. (a). (3 points) Using this data, give a point estimate for the true difference in the proportion of those that ate the burrito and those that did not eat the burrito who developed a gastrointestinal illness.
Answer:
The point estimate is 0.342.
Step-by-step explanation:
Among these children, 145 out of 304 became ill after eating burritos served by their school's cafeteria.
This means that:
[tex]p_B = \frac{145}{304} = 0.477[/tex]
On the other hand, only 20 of the remaining 148 who did not eat burritos became ill.
This means that:
[tex]p_{NB} = \frac{20}{148} = 0.135[/tex]
a). (3 points) Using this data, give a point estimate for the true difference in the proportion of those that ate the burrito and those that did not eat the burrito who developed a gastrointestinal illness.
The point estimate is the subtraction of the sample proportions. So
[tex]p = p_N - p_{NB} = 0.477 - 0.135 = 0.342[/tex]
The point estimate for the true difference in the proportion of those that ate the burrito and those that did not eat the burrito who developed a gastrointestinal illness is 0.342.
Choose the correct order when finding the space between the cylinder and cone. I find the difference of the volumes Il find the volume of the cone III. find the volume of the cylinder
Answer:
D. III, II, then I
Step-by-step explanation:
To find the space between the cylinder and the cone, the first thing to do is: find the volume of the cylinder => next is to find the volume of the cone => then look for the difference in volume between the cylinder and the cone which will give us the space between the cylinder and the cone.
The correct order would be:
III, II, then I
PLS HELP ASAPPPP ASPAP PZLZLZ
Answer:
c???
Step-by-step explanation:
HELP HELP HELP HELP
What is the equation of the trend line in the scatter plot ?
i need help with this math
Answer:
Perimeter = 56
Area = 196
Step-by-step explanation:
We use the Pythagorean theorem to calculate the half-length of the sides (a):
a² + a² = (7√2)²2a² = 7² * 22a² = 98a = 7Half of a side is 7, meaning that the full length is 14.
With that in mind we can calculate the perimeter and area:
Perimeter = 14 * 4 = 56Area = 14² = 196A rectangular garden has length and width as given by the expressions below.
Length: 4 - 7(3x + 4y)
Width: 3x(-2y)
Write a simplified expression for the perimeter of the rectangle.
__ -__x-__y-__xy
Answer:
[tex]P = 8 - 42x + 56y + 12xy[/tex]
Step-by-step explanation:
Given
[tex]Length = 4 - 7(3x + 4y)[/tex]
[tex]Width = 3x(2y)[/tex]
Required
The perimeter (P)
This is calculated as:
[tex]P = 2 * (Length + Width)[/tex]
[tex]P = 2 * (4 - 7(3x + 4y) + 3x(2y))[/tex]
Open bracket
[tex]P = 2 * (4 - 21x + 28y + 6xy)[/tex]
Open bracket
[tex]P = 8 - 42x + 56y + 12xy[/tex]
If x = -3 and y = 4 find the value of : x(3x + 4y)
Answer:
-21
Step-by-step explanation:
(−3)((3)(−3)+(4)(4))
=(−3)((3)(−3))+(−3)((4)(4))
=27−48
=−21
Three pounds of bananas cost $1.47 and 2 pounds of grapes cost $1.18. Which fruit is less expensive per pound? Explain how you know
Answer:
Grapes are less expensive
Step-by-step explanation:
First, find how much money 1 pound of each fruit is:
Bananas: $1.47 / 3 = $0.49
Grapes: $1.18 / 2 = $0.59
Compare:
0.49 < 0.59
So grapes are less expensive
Can someone please help me?
9514 1404 393
Answer:
x = 87°vertical anglesStep-by-step explanation:
The marked angles share a vertex and are formed from opposite rays. They do not share a side, so are not adjacent angles. The angles are vertical angles.
As such, they are congruent, so x = 87°.
What is the surface area of the figure below?
12 ft
Step-by-step explanation:
6 ft+3 ft+3 ft=12 ft
What is the surface area of the triangular prism? 1 5ft 3 ft 5 ft 4 ft
Answer:
134
Step-by-step explanation:
A pharmaceutical sale representative gets paid $50,000 annually plus 3.5% commissions on total sales. This year he sold $420,000 in pharmaceuticals. What are his annual total earnings? someone help pls
Answer:
[tex] \frac{3.5}{100} \times 420000 = 14700commission \\ total \: earnings = 50000 + 14700 \\ = 64700[/tex]
The heights of 4 different people are: 1.55m, 1.52m, 1.81m, and 1.91m. The range of these
heights is:
evaluate the expression for x = 6
3 x + 5 =
Answer:
23
Step-by-step explanation:
6x3=18
18+5=23
Answer
this is wrong
Step-by-step explanation:
this is an equation not an expression. Equations have = and expressions dont. Please rewrite this and I will help.
What is the sum of the first ten terms in a geometric series
with a1=
6 and r = 2?
Answer:
[tex]S_{10} = 682[/tex]
Step-by-step explanation:
Given
[tex]a_1 = 6; r = 2[/tex]
Required
[tex]S_{10[/tex]
This is calculated as:
[tex]S_n = \frac{a(r^n - 1)}{r - 1}[/tex]
So, we have:
[tex]S_{10} = \frac{6 * (2^{10} - 1)}{10 - 1}[/tex]
[tex]S_{10} = \frac{6 * (1024- 1)}{9}[/tex]
[tex]S_{10} = \frac{6 * 1023}{9}[/tex]
[tex]S_{10} = 682[/tex]
if a graph shows no solution what is the inequality
If the number on the other side of the inequality sign is negative, your equation either has no solution or all real numbers as solutions. Use the sign of each side of your inequality to decide which of these cases holds. If the number on the other side of the inequality sign is positive, proceed to step 3.
14x^2=8y^2-6xy where x>0 and y>0 find the ratio x:y
Answer:
4 : 7
Step-by-step explanation:
First, you can start by moving all the terms to one side:
14x^2 + 6xy - 8y^2 = 0
Now we can start to factor this equation in order to find the ratio. We can start by factoring out the GCF, which is 2:
2(7x^2 + 3xy - 4y^2) = 0
In order to factor this equation we multiply the coefficients in front of the x^2 and y^2 term to get: 7 * -4 or -28. We are looking for numbers that have a product of -28 and a sum of 3(as the coefficient of the xy term). These two numbers are 7 and -4. We can rewrite the equation as:
2(7x^2 + 7xy - 4xy - 4y^2) = 0
Now, we can start to factor by grouping:
2( 7x[x + y] - 4y[x + y] ) = 0
And we can factor out [x + y]:
2(x + y)(7x - 4y) = 0
So, we can use the zero product property to get two equations:
x + y = 0
and
7x - 4y = 0
You get:
x = -y
and
7x = 4y
We can get cancel out the first solution because both x and y have to be positive. Rearranging the second equation we can get x : y = 4 : 7
What is the equation of the quadratic function represented by this table ??HELP PLEASE GRADUATION IS JUNE FIRST
9514 1404 393
Answer:
-3, 7, 8
Step-by-step explanation:
You can fill in the boxes from the table values as shown in the attachment.
The leading coefficient is negative because the parabola opens downward. The value of it is the change in y-value as x changes by 1 unit either side of the vertex.
The vertex is identified by the fact that the y-values are symmetrical either side of the vertex.
Answer:
-3, 7, 8
Step-by-step explanation:
3(x+3) [tex]\geq[/tex] 4(x-4)
Answer:
12x2-12x-144 thats the answer
Step-by-step explanation:
Enter an integer to represent the situation.
an elevator ride down 35 stories
Answer:
-35
Step-by-step explanation:
this is a simple but confusing question
however,
since they said down the elevator, and the negative integers reduces, therefore we have our answer as
-35
Please HELP ASAP IN NEED IT I WILL GIVE YOU POINTS
Answer: c six less than twice is the same as two times a number minus six
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
"Twice a number" means a variable/mystery number times 2; aka 2x.
"Six less than" means minus/subtract six.
So, therefore it's 2x - 6.
HELP QUICK PLZ! NO SPAM.
XYZ has vertices X(15,−8), Y(13, 21), and Z(−17, 17). Which of the following represents the translation of △XYZ along vector <−6, 5> and its reflection across the x-axis?
Answer:
X (15, −8) → X ′(9, −3) → X ″(9, 3);
Y (13, 21) → Y ′(7, 26) → Y ″(7, −26);
Z (−17, 17) → Z ′(−23, 22) → Z ″(−23, −22)
Step-by-step explanation:
Use the translation vector <−6, 5> to determine the rule for translation of the coordinates: (x, y)→ (x+(−6),y + 5).
Apply the rule to translate vertices X(15 ,−8), Y(13, 21) , and Z(−17, 17) .
X (15,−8) → (15 + (−6),−8 + 5) → X'(9, −3).
Y (13, 21) → (13+ (−6), 21 + 5) → Y' (7, 26).
Z (−17, 17) → (−17 + (−6), 17 + 5) → Z' (−23, 22).
To apply the reflection across x-axis use the rule for reflection: (x, y) → (x, −y).
Apply the reflection rule to the vertices of △X'Y'Z'.
X' (9, −3) → X'' (9, 3).
Y' (7, 26)→Y''(7, −26).
Z' (−23, 22) → Z'' (−23, −22).
Therefore,
X (15 ,−8) → X' (9, −3) → X'' (9, 3)
Y (13, 21) → Y' (7, 26) → Y'' (7, −26)
Z (−17, 17) → Z' (−23, 22) → Z'' (−23, −22)
represents the translation of △XYZ along vector <−6, 5> and its reflection across the x-axis.
I neeed help on thesse last two my test ends in 3 min help
Answer:
cjones8806
Virtuoso
38 answers
183 people helped
i need points sorry I cant help
Step-by-step explanation:
green box?
(srry if it isn't correct, but that's what I got!!)
rlly sorry